KONFIGURASI SERVANT LEADERSHIP DI PONDOK PESANTREN DARUSSALAM BOGOR - Rahma Karunia; Henni Marlinah (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. This study aims to analyze the configuration of servant leadership at the Darussalam Islamic Boarding School in Bogor. Methods. This research is a qualitative research. Using naturalistic qualitative which tries to reveal the facts of an event in the object being studied as it is to answer the problem by describing the data and the results of its analysis qualitatively. Results. This study proves that the configuration of servant leadership in Pondok Pesantren Darussalam Bogor is carried out by Abu Jihad Lillah as a leader in managing the institution based on, first, pure love for employees. Second, the humility of the leader. Third, the leader has a clear vision so that it is easy to evaluate. Fourth, there is a sense of trust from the leader to the employees. Fifth, there is empowerment carried out by the leader. Implications. The implication of this research is that if a leader in an organization carries out servant leadership, it will increase organizational commitment.